Faktor yang Berhubungan dengan Perilaku Cuci Tangan pada Anak Usia Sekolah - Filia Sofiani Ikasari; Any Zahrotul Widniah (FORIKES, 2022)
Handwashing with soap is one of the most cost-effective public health interventions. The purpose of this study is to review various literature regarding factors related to hand washing behavior in school-age children in Indonesia. This literature review uses the Google Scholar database with the keywords